Safety and efficacy of 650 nm invasive laser acupuncture on non-specific chronic low back pain: A protocol for a multicenter randomized placebo-controlled trial - Jae-Hong Kim; Jae-Hong Kim; Changsop Yang; Jaehee Yoo; Jaehee Yoo; Gwang-Cheon Park; Byoung-Kab Kang; Ae-Ran Kim; Jihye Kim; Dongwoo Nam; Yejin Hong (Frontiers in Medicine, 2023)
BackgroundWe aim to obtain clinical trial data regarding the safety, efficacy, and usefulness of invasive laser acupuncture (ILA) for non-specific chronic low back pain (NSCLBP) through a randomized placebo-controlled trial.MethodsOur clinical trial will be an assessor- and patient-blinded, prospective, parallel-arm, multi-center, randomized placebo-controlled clinical trial. One hundred and six participants with NSCLBP will be allocated evenly to the 650 ILA or control group. All participants will receive education on exercise and self-management. The 650 ILA group will undergo 650 nm ILA for 10 min, and the control group will undergo sham ILA for 10 min per visit, twice a week for 4 weeks, at bilateral GB30, BL23, BL24, and BL25. The primary outcome will be the proportion of responders (≥30% reduction in pain visual analogue scale [VAS] without increased use of painkillers) at 3 days after the intervention ends. The secondary outcomes will include changes in the scores of the VAS, European Quality of Life Five Dimension Five Level scale, and Korean version of the Oswestry Disability Index at 3 days after the intervention ends and 8 weeks after the intervention ends.DiscussionsThe results of our study will provide clinical evidence concerning the safety and efficacy of 650 nm ILA for the management of NSCLBP.Clinical trial registrationhttps://cris.nih.go.kr/cris/search/detailSearch.do?search_lang=E&focus=reset_12&search_page=M&pageSize=10&page=undefined&seq=21591&status=5&seq_group=21591, identifier KCT0007167.